Perlindungan Hukum terhadap Motif Dagang Sarung Samarinda dalam Era Digital - Huda, Nabila; Rustiana (Wadah Inovasi Indonesia, 2024)
The development of digital technology has posed challenges and opportunities for legal protection of traditional trade motifs, such as Sarung Samarinda. This study aims to analyze the legal protection of the Sarung Samarinda trade motif in the context of Law Number 01 of 2024 concerning Information and Electronic Transactions (ITE). The method used in this research is a juridical-normative approach, analyzing applicable regulations and conducting interviews with relevant parties. The research findings indicate that although the ITE Law provides a stronger legal framework, the main challenges lie in the low legal awareness of the public and limited digital supervision. This study recommends the need for collaboration between the government, motif owners, and digital platforms to enhance legal protection and law enforcement against violations of trade motifs in the digital environment.